Influence of Hydrotalcite Containing Corrosion Inhibitormodified by Silane on Corrosion Protection Performance of Epoxy Coating - Anh, Nguyen Tuan; Hoa, Ngo Thi; Hang, To Thi Xuan; Duong, Nguyen Thuy; Truc, Trinh Anh (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 4, 2017)
Abstract: Zinc aluminum hydrotalcite containing 2-benzothiazolythio-succinic acid (HT-BTSA) and modified by 2-aminoethyl-3-aminopropyltrimethoxysilane (APS) at different concentrations (3%, 5% and 10%). APS modified HT-BTSA (HT-BTSA-S) was incorporated in epoxy coatings at 3% concentration. The corrosion protective performance of the epoxy coatings containing HT-BTSA-S were evaluated by electrochemical impedance spectroscopy, adhesion measurement.  The results showed that the presence of HT-BTSA-S improved protection performance of epoxy coating and the best protection was obtained with HT-BTSA modified with 5 % APS.